Orexin neurons in the lateral hypothalamus project to the medial prefrontal cortex with a rostro-caudal gradient. (16th May 2016) - Jin, Jiehua; Chen, Quanhui; Qiao, Qicheng; Yang, Li; Xiong, Jiaxiang; Xia, Jianxia; Hu, Zhian; Chen, Fang
Highlights: Lateral hypothalamic (LH) fibers project to the medial prefrontal cortex (mPFC) with a rostro-caudal hierarchy. LH orexinergic fibers distributes in the mPFC with a rostro-caudal increasing pattern. Distribution of type 1 orexin receptors increased from rostral to caudal mPFC. Abstract: Orexin neurons in the lateral hypothalamus (LH) play an important role in arousal, guaranteeing the execution of medial prefrontal cortex (mPFC)-related higher cognitive functions. The mPFC is anatomically and functionally a rostro-caudal hierarchy. Little is known about the innervation pattern, especially in the rostro-caudal model, from the arousal-promoting orexin system in the LH to the mPFC subregions, including the anterior cingulate cortex (AC), prelimbic cortex (PL) and infralimbic cortex (IL). Here, we used an anterograde tracing method and immunohistochemistry and found that the density of the LH, as well as orexinergic, fibers increased from the rostral part to the caudal part of the mPFC, regardless of AC, PL or IL. Similarly, the distribution of type 1 orexin receptors in the mPFC follows a rostro-caudal increasing gradient hierarchy. These data suggest a rostro-caudal hierarchy of LH orexinergic innervation to the mPFC. We hope to provide anatomical and morphological evidence for the regulation pattern of the arousal-promoting orexin system on the cognition-related mPFC system.